Implementasi Penggunaan Kartu Petani: Sebagai Media Pengendali Distribusi Pupuk Bersubsidi - Ni Ketut Sriwinarti; Andres Faesal (SENTIA 2016, 2016)
The accuracy of the type, quantity, price, place, time and quality are the expectations of the farmers in the process of procurement and distribution of subsidized fertilizer. the various alternatives that have been given or designed apparently not able to overcome the scarcity of fertilizers that often occurs in the community. Usage of farmers Card and construction of information systems in the fertilizer distribution in districts Gerung designed with the hope that can overcome the problems that occur in particular at the line of the end and the inappropriateness in terms of subsidized fertilizer distribution. Each farmer enrolled in farmer groups and listed in RDKK which is then used by the retailer to redeem the fertilizer will receive identity cards. With the identity card of the farmers who own identity can come directly to the retailer and then the retailer can see the profil and fertilizer quota owned by each farmer. with this system, retailers can distribute the fertilizer on target in the right quantity and the right price. In addition the system also helps in viewing the redemption amount that has been done by the retailer and the amount of fertilizer sold.